SIMULATION IMPROVES THE LEARNING RESULT OF CLASS III STATE JUNIOR HIGH SCHOOL 2 IN DAWAN KLUNGKUNG - Muter Adnyani, Anak Agung Istri Rai (Lingual: Journal of Language and Culture, 2015)
This article aims at describing the procedures and the result of the simulation-game as one of the teaching methods. The data was collected from the third-year students of SMPN 2 Dawan taking IPA subject. Observation, direct participation and note-taking were used to collect the data and then analyzed by the range-score postulated by the simulation learning procedure. The result showed that, by applying the simulation method, the students participating in this system managed to improve their ability in IPA (Science) subject